(untitled) (The Journal of Psychology and Sociology, 2015)
The aging ofthe populationchallengesfor the social and economic policy of stateand new opportunities. The social position ofolder peoplein modern conditionsis inseparable from thesocial, political andeconomic changestaking place in society. The growthof the pensionloadreduction andaging ofthe workforce, the growth of the load on thesystem ofhealth and social care, the improvement ofhealth, education, employment oppor tunities andother forms of socialactivity of the population. This category is notdirectly quantifiable. Number of elderly people in Modern Kazakhstan society is growing. The growth of the elderly and older economic, social, moral and ethical behavior have led to a number of consequences. The article is considered an understanding ofthe lifesatisfactionof the elder ly invarious theoreticalapproaches andstudy of the problemof life satisfactionin elderly and senileage.The factorsof wellbeingof older people.The factorsof life satisfactionof older peopleare healthy, individual income, place of residence, social status, having a job.For thewelfare ofan aging societyrequires specificstate policy measures: to ensure the best opportunitiesfor the maintenanceof health, the creation of urban environmentfriendlyto elderly, measures tocontinue work ing, take particular carethe oldest agegroups of the population.